The Effect of Xanthohumol and Thymol on Candida albicans Filamentation and Its Impact on the Structure, Size, and Cell Viability of Biofilms Developed over Implant Surfaces - Enrique Bravo; Marion Arce; David Herrera; Mariano Sanz (Cells)
The aim of this in vitro study was to evaluate the effect of xanthohumol and thymol on the impact of Candida albicans on the structure, size and cell viability of subgingival biofilms formed on dental implant surfaces. The structure and microbial biomass of biofilms developed after 72 h, treated and untreated with both extracts, were compared by scanning electron microscopy (SEM) and confocal laser microscopy (CLSM). Quantitative polymerase chain reaction (qPCR) was used to quantify the number of viable and total microorganisms of each of the biofilm-forming strains in each condition. A general linear model was used to compare and validate the CLSM and qPCR results. The presence of xanthohumol and thymol during biofilm development inhibited the filamentous growth of C. albicans. The biofilm incubated with xanthohumol had significantly lower bacterial biomass and cell viability than the biofilm not exposed to the extract (p < 0.05). In contrast, these global parameters showed no differences when the biofilm was incubated with thymol. In the presence of xanthohumol, there was a decrease in counts and cell viability of Fusobacterium nucleatum, Porphyromonas gingivalis, and Aggregatibacter actinomycetemcomitans. Thymol treatment reduced the viability of F. nucleatum and P. gingivalis. The presence of these vegetable extracts during the development of a dynamic in vitro multispecies biofilm model inhibited the filamentous growth of C. albicans, partially reversing the effect that the fungus exerted on the structure, size and vitality of periodontopathogenic bacteria.